Sense of identity among Samoan migrant women at work and living in Auckland, Aotearoa/New Zealand : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University - Menon, Karin (Massey University, 2009)
This study, leaning on existential phenomenology, explores how the experiences of ‘being working women’ have helped to shape the identities of Samoan women in Auckland. It explores how these women, who grew up within a strong cultural framework and who migrated to New Zealand to engage in work, perceived their transitional processes and how these processes shaped their sense of identity. The focus of the research lies on positive aspects that constitute opportunities for personal development. The objective is to make understood the relationship between being a migrant, being a woman and being at work with regard to identity formation processes. In semi-structured in-depth interviews, twenty Samoan migrant women shared their experiences about coming to Auckland and taking up work. Their accounts were audio-taped, transcribed and analyzed by using a hermeneutic interpretation approach drawing on Heideggerian concepts. In this process, the researcher moved back and forth between the themes evolving from their stories, key patterns and relevant literature about work, migration and sense of identity. The explicated themes and patterns were then compared for consistency with the original accounts of the participants. The study showed that, for women in this study, work played an important part in their identity processes. During the interpretation of the data, the following major domains involved in identity formation by way of ‘being at work’ crystallized: 1) changes in self-views through introspective processes, 2) transformed self-views through relationships with others, 3) self-processes linked to lived space over time. The data analysis showed that the processes in these domains were of an interacting, reciprocal nature. It also showed that the changes in the participants’ sense of identity were created by reflective processes such as internal dialogues. Having reassessed and changed some of their ways of ‘being and doing’ created changes in the participants’ roles in relationships with others. As their status changed from being positioned as not-knowers to being acknowledged as employees who had unique skills to offer to their colleagues, the participants underwent changes from being ‘outsiders’ to becoming ‘insiders’ at work. The participants’ increase in status at work, in return, gained them status as experts, advisors and advocates in their families and community. Elders and males who initially opposed these women’s career ambitions at work now acknowledged them as experts in their field of work or as professionals who were in a position to assist and support them in a number of ways. The changing understanding in the wider socio-cultural environment about Samoan women’s choices shaped how they experienced their life-worlds and, ultimately, perceived themselves. These identity processes continued ‘over time in historical space’; they changed the participants’ — and ultimately other Samoan women’s — social standing at their workplaces and in their community. The participants’ accounts indicated that being in paid work served a number of purposes, such as financial and personal autonomy and having more control over their choices about the ways they wanted ‘to be’ and ‘do things’. Over time, for the participants, the benefits of being in paid work in relation to their self-development were: a) moving from shyness and insecurity to increased levels of assertiveness, autonomy and control over their lives through exploring and applying their strengths, b) moving from not-belonging and being ‘strangers’ to being part of the ‘home-group’ through affiliation with others at work, and c) increased social status and roles as change agents at work, in their family and community through transferring cultural knowledge and work skills across these domains, and thereby contributing to changes in their cultural environments over time and across space. In conclusion, for the Samoan migrant women in this study, ‘being in paid work’ was experienced as more than a source of sustaining their existence. In particular, ‘being skilled working women’ added to their sense of identity via opportunities to explore their latent skills and develop new competencies. Likewise, for women in other cultures, migration and work can provide opportunities for personal development not accessible in their country of origin.
Keywords: Samoan women; Samaon immigrants; Identity; Auckland; New Zealand; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380105 Social and community psychology